Strategi Pengembangan Pariwisata Berkelanjutan Sebagai The Regency Of Sport Tourism - Rizki Bastanta B Manalu; Joen Parningotan Purba; Samuel Suranta Barus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to identify the potential and actual conditions of sports tourism, analyze internal and external factors that influence its development, and formulate effective strategies to strengthen Samosir's competitiveness and image as a leading sports tourism destination. The method used is a qualitative descriptive approach with a SWOT analysis. The results show that the development of Samosir's sports tourism is in Quadrant I (aggressive strategy), with external opportunities (O = +1.86) and internal strengths (S = +1.53) more dominant than weaknesses and threats. Therefore, expansion and innovation strategies through branding strengthening, digital promotion, human resource capacity building, and sustainable environmental management are key to Samosir's growth as a competitive sports tourism destination nationally and internationally. In conclusion, Samosir Regency has great potential to develop sustainable tourism through expansion and innovation strategies Keywords: Development strategy; tourism; sustainable